Application of inorganic passivators reduced Cd contents in brown rice in oilseed rape-rice rotation under Cd contaminated soil. (November 2020) - Huang, Suihua; Rao, Gangshun; Ashraf, Umair; He, Longxin; Zhang, Zezhu; Zhang, Huailin; Mo, Zhaowen; Pan, Shenggang; Tang, Xiangru
Abstract: Immobilization of heavy metals by the application of chemical amendments is an eco-friendly, economical and effective method to remediate cadmium (Cd) -contaminated soils. Field experiments were conducted during 2016–2018 following oilseed rape-rice rotation with the application of inorganic passivators i.e., slaked lime (CaOH2 >95%) and sepiolite (SiO2 >50%, MgO>20%). The experimental treatments were comprised of: rice planting in winter fallow and without passivator (F-PA0); fallow with slaked lime (F-PA1); fallow with sepiolite (F-PA2); oilseed rape–rice rotation without passivator (R-PA0); rotation with slaked lime (R-PA1); and rotation with sepiolite (R-PA2). The slaked lime and sepiolite were applied after the harvest of rape at 2000 and 5000 kg ha −1, respectively. Results revealed that the Cd contents were reduced by 47.44–49.03% in brown rice for F-PA2 and 9.54–42.66% in soil for R-PA2. The superoxide dismutase (SOD) activity was decreased by 10.65–17.98%, the malondialdehyde (MDA) contents were reduced by 28.57% whereas the proline content was decreased by 32.61% under R-PA2. In addition, the filled grain percentage was improved by 6.87% (F-PA2) and 3.70% (R-PA1), respectively. Overall, rice sown after oilseed rape gave better yields than sown after fallow fields while application of slaked lime and sepiolite as passivator could be a potential management option to grow crops in metal polluted soils. Graphical abstract: Image 1 Highlights: Slaked lime and sepiolite application reduced the Cd contents in brown rice. Planting winter rape and passivator application increased soil pH. Antioxidant activities were regulated by passivator application under Cd stress. Rice sown after oilseed rape gave better yields than sown after fallow fields.